A MAN AHEAD OF HIS TIME: HEZEKIAH WOODWARD. A CONSIDERATION OF THE SEVENTEENTH-CENTURY VISIONARY’S VIEWS ON TEACHING THE YOUNG IN ENGLAND - Smoluk, Marek (European Scientific Journal, ESJ, 2013)
As early as in the first half of the 17th century a steady outflow of critical views and advice about education was to be heard from English educationalists and would-be-reformers. One of the voices which particularly stood out was that of Hezekiah Woodward. An analysis of Woodward’s ideas discussed in this paper, is preceded by a brief presentation of the state of schooling in the early Stuart age in order to determine whether or not the educationalist’s views were in concert with the realities of those days. Woodward, having become acquainted with The Great Didactic by Comenius, decided to rebel against the accepted practices in schools, and consequently chose to work out his own ideas. This paper provides evidence that the educationalist’s proposals aimed at reforming seventeenthcentury education were well ahead of their time. He advocates a greater sense of responsibility on the part of the school and its masters, the parental duty to participate in moral and religious instruction and teaching through the senses; as well as a clearly-expressed belief that handicapped children are equally worthy of being educated. With this approach, Hezekiah Woodward made a name for himself. Though discarded at the time, his ideas became a basis for a modern viewpoint of contemporary education.